GIRLS NOT BRIDES’S INTEREST IN ENDING CHILD MARRIAGE IN NIGERIA 2014-2019 - Dhea Syafira; Tri Joko Waluyo (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This study's focus is to analyze the motivation of the Girls Not Brides organization in dealing with early childhood problems in Nigeria. Child marriage is a practice that violates human rights because it causes various kinds of impacts both on the child and even the country itself. Nigeria has ratified international and regional instruments regulating children's rights, including child marriage.This research used library research. The data sources used are primary data and secondary data from press releases and data from child marriage in Nigeria or worldwide. The data will be analyzed with descriptive analysis method. The base theory used is role theory with a pluralism perspective.From the data analysis, it was concluded that child marriage is a practice that violates Girls' Human Rights and causes a lot of harmful impacts for the children, family, to their environment. Girls Not Bride's interest in ending child marriage is for girls to enjoy the equality of degree with boys, reach their full potential and reach the 5.3 Target of Sustainable Development Goals, which could not be achieved without ending child marriage.Keywords: Child Marriage, Girls Not Brides, Nigeria, SDGs, and Human Rights